From A National, Centrally Planned Health System To A System Based On The Market: Lessons From China - Ma, Jin; Lu, Mingshan; Quan, Hude (Health Affairs, 2008)
No other country has undergone health care reforms as dramatic as China's. Starting in 1978, China reformed its health system from a governmental, centrally planned, and universal system to a heavily market-based one. Now, three decades later, the Chinese government openly acknowledges that the reforms failed and seeks new directions. This paper adds to the literature by examining China's health care from a system perspective, describing its health services delivery, access, outcomes, and population health in the post-reform era. It also identifies the main issues in the current system and highlights the key lessons learned from China's reform process.